Segregation of Women and Aboriginal People Within Canada's Forest Sector by Industry and Occupation - Mills, Suzanne E. (The Canadian Journal of Native Studies, 2006)
This study examines employment segregation by gender and by Aboriginal ancestry within Canada's forest sector in 2001. Results show that while gender segregation was principally by occupation, segregation by Aboriginal ancestry was principally by industry sub-sector. White women were over represented in clerical occupations and Aboriginal men were over represented in woods based industries. Patterns of employment for Aboriginal women differed from those of both Aboriginal men and white women.
Keywords: Employment; Ethnic Interests; Forest products industry; Gender equity; Native North Americans; Native People; Native women; Occupations; Segregation